Constructing a vocabulary list of english textbooks in semantics and pragmatics - Lee, Hye Kyung; Kim, Hyeon Okh (Korean Journal of English Language and Linguistics, 2020)
This study aims to develop a vocabulary list of semantics/pragmatics and to complement an existing academic vocabulary list in general linguistics. For that purpose, a semantics/pragmatics corpus (SPTC) consisting of approximately 1,400,000 words was compiled. By combining both a quantitative analysis (i.e., AntWordProfiler) and a qualitative manual examination, a semantics/pragmatics vocabulary list was constructed of 409 word families out of the corpus. The compiled list was then compared with an existing introductory linguistics word list to identify lexical patterns that were common with general linguistics and unique to semantics/pragmatics. The results of the analysis showed that a set of (sub-)technical terms characterized the semantics/pragmatics texts, which suggests the need for a specialist vocabulary list for students in semantics and pragmatics. The result also showed that the semantics and pragmatics texts feature a more frequent use of specific conjunct adverbs including hence, which proved to be instrumental in presenting key terms and topics and organizing the flow of arguments. This might have been because semantics/pragmatics texts are richer with technical terms than are introductory linguistics texts. Pedagogical implications and directions for future research are also suggested.
Keywords: Academic vocabulary; Linguistics vocabulary list; Semantics/pragmatics vocabulary list; Technical terms